2017
DOI: 10.1111/cas.13400
|View full text |Cite
|
Sign up to set email alerts
|

WASH overexpression enhances cancer stem cell properties and correlates with poor prognosis of esophageal carcinoma

Abstract: There is increasing evidence that cytoskeleton remodeling is involved in cancer progression. Wiskott‐Aldrich syndrome protein (WASP) family represents a key regulator of actin cytoskeleton remodeling. However, the underlying mechanism of the WASP family in cancer progression remains elusive. Here, we studied the role of WASP and SCAR Homolog (WASH), a recently identified WASP family member, in human esophageal squamous cell carcinoma (ESCC). Using three human ESCC cell lines, we found that WASH expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Mouse and human WASH orthologs are essential genes that are needed many times throughout development. For example, conditional knockdown of WASH in mouse hematopoietic stem cells results in defective blood production associated with severe cytopenia and anemia (Xia et al, 2014), whereas human WASH genes are at heightened risk for deletions/rearrangements, are upregulated in invasive breast cancers and their overexpression correlates with poor prognosis of esophageal cancers (Huang et al, 2017;Leirdal et al, 2004;Linardopoulou et al, 2007;Nordgard et al, 2008). In addition, the SHRC components of WASH are linked to neurodegenerative disorders, including hereditary spastic paraplegias, Parkinson disease and Hermansky-Pudlak syndrome (Elliott et al, 2013;Freeman et al, 2013;McGough et al, 2014;Ropers et al, 2011;Ryder et al, 2013;Turk et al, 2017;Valdmanis et al, 2007;Vardarajan et al, 2012;Zavodszky et al, 2014a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse and human WASH orthologs are essential genes that are needed many times throughout development. For example, conditional knockdown of WASH in mouse hematopoietic stem cells results in defective blood production associated with severe cytopenia and anemia (Xia et al, 2014), whereas human WASH genes are at heightened risk for deletions/rearrangements, are upregulated in invasive breast cancers and their overexpression correlates with poor prognosis of esophageal cancers (Huang et al, 2017;Leirdal et al, 2004;Linardopoulou et al, 2007;Nordgard et al, 2008). In addition, the SHRC components of WASH are linked to neurodegenerative disorders, including hereditary spastic paraplegias, Parkinson disease and Hermansky-Pudlak syndrome (Elliott et al, 2013;Freeman et al, 2013;McGough et al, 2014;Ropers et al, 2011;Ryder et al, 2013;Turk et al, 2017;Valdmanis et al, 2007;Vardarajan et al, 2012;Zavodszky et al, 2014a,b).…”
Section: Discussionmentioning
confidence: 99%
“…WASH, a newly identified member of the WASP family, can regulate actin formation on the surface of the endosomal membrane to form a reticular scaffold, thus participating in regulation of transferrin recycling ( 34 ). Furthermore, in esophageal cancer, WASH overexpression improves the characteristics of tumor stem cells and is associated with a poor prognosis ( 35 ). The above results suggest that the WASP family may play a role as a pro-oncogene in tumors, in which the WASH complex may promote tumor cell development by regulating actin filament cytoskeleton remodeling, but the exact mechanism is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a clinical study on esophageal carcinoma showed that overexpressed WASH maintained the stem cell phenotype of cancer cells by promoting IL-8 production, thus promoting the progression of the carcinoma. Additionally, in vivo experiments found that the inhibition of WASH expression slowed the progression of tumors, which suggests WASH be a potential target to intervene in human esophageal carcinoma ( 330 ).…”
Section: Related Diseasesmentioning
confidence: 99%